Flow behaviors and residual oil characteristics of water flooding assisted by multi-effect viscosity reducer in extra heavy oil reservoir. (18th June 2023) - Shi, Wenyang; Xu, Lilong; Tao, Lei; Zhu, Qingjie; Bai, Jiajia
Abstract: Although waterflooding treatment assisted by traditional viscosity reducer yields additional oil recovery, this increments in production sometimes cannot meet the production requirements. To solve this problem, it is necessary to analyze and understand the flow mechanism of heavy oils in the waterflooding process assisted by the viscosity reducer. This study employed an etched glass micro-model to visualize the flow behavior of heavy oils under assistance of a novel multi-functional viscosity reducer with the condition of high temperature and ultra-heavy oil. The water flooding and novel viscosity reducer flooding experiments were carried out, and the state and shape of the remaining oil phase were observed from the global perspective and the microscopic local perspective in the etching micro-glass. Results show that the viscosity reducer solution can not only greatly reduce viscosity of heavy oil but also decrease oil-water interface tension. In the waterflooding process, the continuous oil group and long oil slug are the main characteristics of remaining heavy oil in the reservoir. By waterflooding with the new viscosity-reducer, the remaining oils exist as short slug and droplet, and 3 times wider flooding area for fluid-flow was observed than conventional waterfloodings.